PSYCHOLOGICAL ANALYSIS OF THE MAIN CHARACTER IN PAULO COELHO’S THE ALCHEMIST - Gharizata, Galih (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThis topic was chosen to get more understanding about the main psychology character of Santiagoin the novel and the conflicts faced by the main character. The main character in the novel interactswith the character in the story and plays an important role. The data was taken from the novel TheAlchemist. The data was collected through the documentation by using note-taking and reading.The first step of collecting data was to read the novel frequently and intensively. Then, the secondstep was to identify and classify the data to find out the relevant statement in the novel that can berelated to intrinsic and extrinsic elements. There are two different theories used in analyzing thestudy, and those are the psychology theory and the conflict theory. The psychology theory that isused in this study is the theory proposed by Bernhardt (1953), who analyzed the psychology of themain character. The conflict theory that is used is the theory proposed by Kenney (1966). Thisstudy is conducted on how the psychological aspect influence the main character and whatconflicts affect his personality. The conclusions of this study are as follows: Santiago, as the maincharacter in the story, is faced with many internal conflicts that shaped his psychologicalmotivation, appetite, and emotions. It shows that psychology and conflict had a great impact oneach other in the development of character.Keywords: main character, psychological analysis, literature.ABSTRAKTopik ini dipilih untuk lebih memahami psikologi tokoh utama Santiago dalam novel dan konflikyang dihadapi tokoh utama. Karakter utama dalam novel berinteraksi dengan karakter dalamcerita dan memainkan peran penting dalam cerita itu sendiri. Data diambil dari novel TheAlchemist. Pengumpulan data dilakukan melalui dokumentasi dengan cara mencatat danmembaca. Langkah awal pengumpulan data adalah sering membaca novel secara intensif.Kemudian, langkah kedua adalah mengidentifikasi dan mengklasifikasikan data untuk mengetahuipernyataan relevan dalam novel yang dapat dikaitkan ke dalam unsur intrinsik dan ekstrinsik. Adadua teori berbeda yang digunakan dalam menganalisis penelitian ini, yaitu: teori psikologi danteori konflik. Teori psikologi yang digunakan dalam penelitian ini adalah teori yang dikemukakanoleh Bernhardt (1953) yang menganalisis psikologi tokoh utama. Teori konflik yang digunakanadalah teori yang dikemukakan oleh Kenney (1966). Penelitian ini dilakukan tentang bagaimanaaspek psikologis mempengaruhi karakter utama dan konflik apa yang mempengaruhikepribadiannya. Kesimpulan dari penelitian ini adalah sebagai berikut: Santiago sebagai tokohutama dalam cerita dihadapkan pada banyak konflik internal yang membentuk motivasipsikologis, nafsu makan, dan emosinya, ini menunjukkan bahwa psikologi dan konflik memilikidampak besar satu sama lain dalam perkembangan karakter.Keywords: karakter utama, analisis psikologis, sastra.